MORUS INDICA: ANTIOXIDANT ACTIVITY IN FOOD AND BIOLOGICAL SYSTEMS - VANITHA REDDY P; ASNA UROOJ (International Journal of Pharma and Bio Sciences, 2013)
Morus Indica-MI (Mulberry) varieties M5, V1 and S36 leaves were analyzed for their phytochemical composition and antioxidant potency of 100% methanol (M), 80% M (M& water), dechlorophyllised, aq. cold and hot extracts in food and biological system. The radical scavenging activity (RSA), reducing power assay, FRAP and inhibition of oxidation in oil and microsomes was evaluated at different concentrations. Among three varieties, S36 was rich in phytochemicals. All the extracts of MI varieties have performed in a dose dependent manner. The dechlophyllised extract of all the varieties have shown significantly (P <0.05) high RSA, reducing power and inhibition of oxidation in oil and microsomes. Also the IC50 of S36 in RSA and activity in oil and microsomes was significantly (P<0.05) high. Above results indicate that the MI varieties can be used as nutraceutical in preventing or reducing the oxidative stress at the biological level and also as functional ingredient in health food formulations.